Problems of the studyof ancient Turkish writingat school. (Eurasian Journal of Philology Science and Education, 2015)
The article highlights the problem of system approach in teaching of ancient Turkish writingat school.The ancient Turkish runic writing reflects the ideology and introduces the concept of a centralized state as the guarantor of the freedom and independence of the Turkish people, which has had a common history and a common culture of origin for centuries, and also it has become their common heritage.Itlaid theinexhaustible energy andstrong willof Turkishalemakersregardinganything related tosuch sacrednotions as"people", "State", "freedom», «independence”.Monuments of Ancientwriting –is an extremely valuablesource for thelanguage, history,ethnogenesis, geography, written culture.They are witnesses of a high-levellanguageculture and statehoodancestorsof the Kazakh people.
Keywords: monuments; valuable source; independence; language culture